The effect of government support, satisfaction and social on motivation in e-sports engagement among athletes in Kuala Lumpur secondary schools - Amran, Shaheliza; Mohamed Haidi, Mohd Yazid; Samsudin, Shamsulariffin; Salleh, Kaswati (Zibeline International, 2023)
This study aims to investigated if there is an influence between government support, satisfaction and social on the level of motivation. This is a quantitative study using a cross-sectional study method involving 108 e-sports athletes (L=60, P=48) conducted in Secondary Schools around Kuala Lumpur. Research was conducted using a questionnaire as a research instrument using a likert scale format. Findings of the study for government support mean score which is (M=2.70, SP=1.22), while for satisfaction the mean score (M=4.01, SP=0.94) social influence mean score (M=3.73, SP=0.74) and motivation mean score (M=4.08, SP=0.93). Independent sample t-test was used to see the gender difference between each variable and results of the analysis showed satisfaction, social influence and motivation (p >0.05) explaining that there was no significant difference between men and women. To see the relationship between government support, satisfaction and social influence on the level of motivation, correlation analysis was used and the results showed that satisfaction has a high positive relationship with value (r=0.877**, p=0.000). So the regression test is used to see the factors that influence government support, satisfaction and social influence on the level of motivation and results show the highest percentage of influence which is 77.6%. Therefore, overall, the level of motivation is not only influenced by government support because the R Square value shows only 6.4%.